(untitled) (GYMNASIUM, 2017)
Angina pectoris is a more or less intense coronary symptom, more or less severe, according on the associating pathology. Stable effort angina is less severe than the stable resting angina, both being less severe than the unstable angina. Taking into consideration the fact that alongside the basic treatment of this coronary disease and the emergency nitroglycerin treatment, a series of physical manifestations caused by repeated angina crises can be approached through Shiatsu and stretching, we have structured and applied a specific program on six patients with stable angina, and compared their results with the results of other six patients with the same pathology, but who only received drug treatment. The results have proven that the application of specific Shiatsu and stretching programs on stable angina patients over the course of eight weeks (three sessions per week during the first four weeks, and two sessions per week during the following four) contributes more than the drug treatment to the decrease of the intensity, frequency and duration of angina crises.